The Tondo project whom have we served - Lindauer, David L. (Philippine Journal of Public Administration, 1981)
The Tondo Foreshore community is a beneficiary of a slum upgrading program sponsored by the World Bank, designed to provide adequate housing for approximately 200,000 people. Empirical findings, however, show that a substantial number of the beneficiaries do not belong to the specified poverty group. The community is characterized by heterogeneous income, and a proliferation of multi-story dwellings and well-constructed homes are evident. For a more meaningful realization of housing pr ograms and for a better appreciation of the relationship between poverty and inadequate housing, it may be well to consider the formulation and implementation of policies to achieve specific poverty objectives.